Surveillance and public security: prejudices and social segregation widened by the alleged digital neutrality - Miranda, Pedro Fauth Manhães (2020)
This article attends to demonstrate how the new algorithmic implementations, allegedly unbiased, accentuate discrimination and prejudice through the surveillance mechanisms. When personal information about the population is applied to the development of artificial intelligence technologies, in a society already marked by selectivity, the consequences can be catastrophic. The starting point is given by the analysis on surveillance, updated by Zygmunt Bauman, describing how the information society was shaped and gained the form it has today. Then, through a bibliographic review based on a deductive method, it is possible to observe that in countries where there is a permanent feeling of insecurity and racial discrimination has become institutionalized, the lack of transparent use of predictive algorithms, especially by criminal justice, causes negative effects on effectiveness of public policies, making more and more victims and accentuating disparities, instead of promoting security.